E-learning for accounting science from the viewpoint of members of the teaching staff and students of the accounting department in various Sudanese universities (Entrepreneurship Journal for Finance and Business, 2020)
This research aims to introduce electronic education and introduce the science of accounting as a science that can be taught electronically and to identify the most important challenges that face it in terms of addressing the technical and technical challenges and challenges facing the accounting student, the challenges facing the accounting teacher and the challenges facing the teaching of accounting electronically, Research’ importance in terms of scientific importance lies in addressing the scientific definitions of to the research related concepts topic. The practical importance lies in the possibility of seeing the opinions of students and professors of accounting science in the most important challenges facing the teaching of accounting electronically as the researcher follows In this research the descriptive and analytical approach in presenting the challenges facing e-learning for the science of accounting through the applied study and through the above, it is possible to arrive at contents that suggest the most important technical challenges represented in the weakness of the network and the means of scientific communication through the conference programs and the challenges facing the subject teacher from the difficulty of the effort Exerted in controlling and managing the huge number of students simultaneously, the difficulty of scientific explanation of the accounting subjet electronically, the difficulty of scientific recording of accounting electronically , the difficulty of conducting accounting operations electronically , the difficulty of conducting accounting operations electronically and the difficulty of providing electronic tools for use in accounting teaching and the smallness of computer screens, which causes Confusion in reading values ​​and financial numbers and commenting Albram C. Educational and internet disconnection during the lecture leads to your Lord in the delivery of accounting information. It is considered one of the most important obstacles in the field of teaching accounting electronically. The researcher also recommends educational institutions that contribute to the progress of the e-learning process after workshops and recovery courses.